Estetika Ekologi Pada Yoga Surya Tradisi Watukaru Di Pasraman Seruling Dewata Desa Pakraman Bantas, Kecamatan Selemadeg Timur, Kabupaten Tabanan - I Wayan Nerta (Jurnal Yoga dan Kesehatan, 2020)
Yoga is the reunification of all thoughts, intellect, feelings, emotions, instincts, and other traits. Āsana is steady, calm and comfortable posture. The yoga āsana movements contained in it are quite beneficial for the body and mind. The inspiration from the yoga āsana movement is also inseparable from the forms of living beings and nature. Every object in the universe and organic object forms has its own amazing structure. Thus, through an aesthetic approach, it is known the value of beauty, various forms, and the influence of internalization and modification of natural movements and living beings in āsana yoga. Maintaining the body to keep it clean, healthy and strong is a daily duty and responsibility. Solar yoga is a yoga attitude as a way to increase spiritual awareness and enlightenment by respecting and worshiping the sun. Pasraman Seruling Dewata is one of the non-formal institutions to study Hinduism in relation to the existence of Balinese cultural traditions. Many classical Yoga teachings are taught there, the Watukaru tradition of solar yoga is one of them. The solar yoga movement has benefits and meaning as well as ecological aesthetic value. Based on this, it is necessary to know the form of the Watukaru tradition solar yoga, the internalization of ecological aesthetics in the Watukaru tradition solar yoga and the implications of the Watukaru tradition of solar yoga for students at Pasraman Seruling Dewata, Pakraman Bantas Village, East Selemadeg District, Tabanan Regency.